B1 HTT CAG knock-in mice with pure and interrupted repeat tracts provide insight into the role of somatic expansion in HD pathogenesis. (13th September 2016) - Wheeler, Vanessa C; Kovalenko, Marina; Giordano, James; Andrew, Marissa; Menalled, Liliana; Alexandrov, Vadim; Thiede, Christina; Weidner, Jenny; Teichmann, Kerstin; Tottey, William; Cumming, Sarah A; Correia, Kevin; et al.
Abstract : Background: The expanded CAG repeat in the Huntington's disease (HD) gene HTT is the major contributor to disease onset. The repeat also expands progressively in somatic cells, particularly in medium-spiny striatal neurons. Human and mouse genetic studies strongly support somatic expansion as disease modifier, with important implications for developing novel disease-modifying therapies. Aim: To develop HD knock-in mice to gain further insight into the role of somatic CAG expansion on phenotypic expression. Methods/techniques: We have generated HD knock-in mice harbouring either pure CAG tracts (HttCAG45, HttCAG80, HttCAG105) or CAG tracts interrupted with CAA residues (Htt[CAGCAACAGCAACAA]9, Htt[CAGCAACAGCAACAA]16, Htt[CAGCAACAGCAACAA]21), with pairs of mice expressing huntingtin with matching glutamine tract lengths. We have analysed somatic expansion, huntingtin expression and performed phenotypic analyses. We examined the effect of repeat interruption on quantitative nuclear huntingtin immunstaining phenotypes in the striatum, and on behaviour using automated, high-throughput PhenoCube®, NeuroCube® and SmartCube® platforms. Results: Pure repeat mice exhibit tissue-specific, age- and CAG length-dependent somatic expansion. In contrast, the [CAGCAACAGCAACAA] repeat configuration results in complete repeat stabilisation. Interestingly, repeat interruption also reduces huntingtin mRNA and soluble protein. The results of our phenotypic analyses provide evidence for slowed disease progression in the interrupted repeat mice relative to their pure repeat counterparts. Conclusions: These results are consistent with the hypothesis that somatic expansion accelerates pathogenesis. However, additional molecular and phenotypic analyses are needed to tease out the relative contribution of somatic expansion to disease expression. Together, the results from these experiments will provide important insight into the role of somatic expansion in HD, as well as insight into other aspects of disease biology that are dependent upon HTT CAG repeat DNA and/or RNA structure. Importantly, these novel knock-in lines provide valuable tools to dissect mechanisms of HD modifier genes that might act in a manner that is either dependent on or independent of somatic CAG expansion.